Penerapan Fungsi-fungsi Manajemen dalam Pengelolaan Perpustakaan di Madrasah Aliyah Swasta Hidayatullah Tanjung Morawa - Julianti, Risma; Yulia, Fitri; Zuliana, Eka (Medan Resource Center, 2025)
This study aims to examine the application of management functions in the administration of the library at Madrasah Aliyah Swasta Hidayatullah Tanjung Morawa, as well as to identify supporting and inhibiting factors within the process. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation involving school principals, librarians, teachers, and students. The findings reveal that the core management functions—planning, organizing, implementing, and supervising—have been implemented in library management, although improvements are still needed. Key supporting factors include the involvement of the foundation, local community, and regional government, which play a significant role in optimizing library services. A notable contribution of this study is the active synergy between the school and its surrounding environment in promoting a literacy culture through initiatives such as mobile libraries and village-based libraries. This distinguishes the research from prior studies that focused primarily on internal school dynamics without acknowledging the tangible contributions of external stakeholders. Furthermore, the school’s strategic plans to expand library facilities and enhance librarian competencies demonstrate a sustained commitment to strengthening school-based literacy management.